2013
DOI: 10.2478/botlit-2013-0013
|View full text |Cite
|
Sign up to set email alerts
|

Changes in botanical diversity of sown grasslands due to naturalization and extensive management

Abstract: Sendžikaitė J., Pakalnis R., Gudžinskas Z., 2013: Changes in botanical diversity of sown grasslands due to naturalization and extensive management [Sėtų pievų botaninės įvairovės kaitos dėl žolynų natūralėjimo ir ekstensyvaus naudojimo]. -Bot. Lith., 19(2): 99-110The paper deals with sown grassland naturalization models related to changes in botanical diversity of extensively managed meadows under temperate climate conditions. The vegetation surveys were carried out in Sėliškės and Polyma Experimental Field St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…The short‐term treatments decreased the frequency of large perennials (like Arrhenatherum elatius ) and increased the frequency of annuals (like Medicago lupulina or Picris hieracioides ), often observed in the early stages of succession. The same tendency was found under long‐term mowing and grazing management: the dominance of short annuals and an increase in vegetatively spreading species when compared to the controls, which was also observed by Sendžikaitė et al (2013). Other findings concluded that short‐term mowing treatments were more effective at reducing the stem density of the invader than with long‐term mowing as a management tool.…”
Section: Discussionsupporting
confidence: 84%
“…The short‐term treatments decreased the frequency of large perennials (like Arrhenatherum elatius ) and increased the frequency of annuals (like Medicago lupulina or Picris hieracioides ), often observed in the early stages of succession. The same tendency was found under long‐term mowing and grazing management: the dominance of short annuals and an increase in vegetatively spreading species when compared to the controls, which was also observed by Sendžikaitė et al (2013). Other findings concluded that short‐term mowing treatments were more effective at reducing the stem density of the invader than with long‐term mowing as a management tool.…”
Section: Discussionsupporting
confidence: 84%